Fragments Re-Connected: Identifications of leaves stemming from the same twelfth-century or early thirteenth-century missals now divided between the collections of the National Library of Finland and the National Archives of Sweden - Tahkokallio, Jaakko (Mirator, 2023)
The large fragment collections of the National Archives of Sweden and National Library of Finland share the same early modern history of recycling. Because of this, leaves from one medieval manuscript are often divided between these two collections. This article establishes a series of new inter-archival connections between fragments stemming from the same book. It focuses on missal fragments dated to the twelfth or early thirteenth century. In addition, it presents preliminary observations on how the recycling history helps us to contextualise the fragments preserved in Finland as historical evidence.